THE RELATIONSHIP BETWEEN SOCIAL NETWORK SITES USE, STRESS, ANXIETY AND DEPRESSION SYMPTOMS AMONG UNIVERSITI SAINS MALAYSIA (USM) STUDENTS DURING THE COVID-19 PANDEMIC - Kseniia Kondratenko; Awang Bono, Suzanna; Weng-Tink Chooi (SARJANA, 2024)
Social media has become a tool that facilitates almost all areas of our lives be it shopping, work, entertainment. However, the rate of consumption of social network sites (SNS) increases during natural disasters, military conflicts and states of emergencies such as the recent Covid-19 pandemic. This occurs due to various factors ranging from the necessity to stay updated about recent news and measures to the need for escaping from negative affect such as stress, anxiety and depressive symptoms. However, SNS can become a source of heightened stress, anxiety and depression symptoms if not well managed or used excessively. The aim of the current study is to investigate the relationship between SNS use, stress, anxiety and symptoms of depression in the context of Covid-19 pandemic. Additionally, the study attempted to establish the criteria to measure excessive SNS use. A total of 266 participants aged 18-26 years old students of a public university in Penang, Malaysia completed an online survey containing SNS use self-report, Bergen’s Social Media Addiction Scale (BSMAS) and Depression, Anxiety, Stress scale (DASS-21). Findings suggested a significant relationship between SNS use and stress, and SNS use was not a significant predictor for anxiety and depression levels. Additionally, the findings showed that in accordance with BSMAS mean scores and SNS daily use of the current sample, more than 4 hours of SNS use could be considered as excessive. If excessive use was defined as a discrepancy between current and ideal SNS use and BSMAS scale, an interval of more than 1 hour between actual and ideal SNS use is to be considered as excessive.